Values at work: a case of labourers in agribusiness (Jordan) - Mauro Van Aken (Revue des Mondes Musulmans et de la Méditerranée)
In a context that has been reshaped in the last half a century by conflict and displacement, the peculiar borderland that divides the Jordanian east bank from the Occupied Territories in the West bank, has been transformed due to intensive rural modernisation, a process that has generated new ideas and values of work and of working persons. Palestinian refugees have settled among Jordanian Bedouins, the Ghawarneh tribe and after the 1970s, Egyptian labourers and a smaller Pakistani community and have shaped a context where terms of belonging are daily at work and overlap on the new agribusiness. The paper focuses on the different ideas and practices of work activated by local actors and their cultural understanding of the new categories of labour, cultural perceptions that are crucial part of local identity definitions and of social borders. A special focus on marginal communities helps in highlighting the hierarchy that has set up in the valley and the changing meanings of wage relations enmeshed in ethnic and class definitions.